THE EFFECT OF TEMPERATURE ON THE STABILITY OF NUCLEIC ACIDS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Nucleic acids play a central role in the storage, transmission, and expression of genetic information, and their structural stability is essential for normal cellular function. Temperature is one of the key physical factors that significantly influences the stability, conformation, and biological activity of DNA and RNA molecules. Changes in temperature can induce structural transitions such as denaturation, melting, and renaturation, thereby affecting hydrogen bonding, base stacking interactions, and molecular flexibility. This article analyzes the bio-physical mechanisms underlying the temperature-dependent stability of nucleic acids, with particular emphasis on DNA double-helix melting behavior and RNA secondary structure alterations. Experimental approaches and theoretical models used to study thermal stability, including melting curves and thermodynamic parameters, are also discussed. Understanding the temperature effects on nucleic acid stability is crucial for molecular biology, biotechnology, and medical diagnostics.